Effectivenes of Lactobacillus plantarum 1UHCC bacteria in partial hydrolysis of goat bone in producing gelatin. Issue 1 (April 2020) - Hasma,; Abustam, E; Malaka, R; Said, M I; Nahariah, N; Laga, A
Abstract: Gelatin was obtained from the bones of goats that are hydrolyzed in several stages. In the initial stage, immersion is carried out using an acid solution so that the goat's bones can be partially hydrolyzed and the connective tissue of the bone becomes loose so that the gelatin can be easily extracted. Partial hodrolysis in goat bones using chemical acids has been widely used but very few utilize biological acids produced by Lactic Acid Bacteria (BAL), specifically Lactobacillus plantarum . Therefore, it is necessary to grow lactic acid bacteria in maintenance media to produce lactic acid as a preservative in the bones. This study aimed to obtain preliminary information to determine the ability of L. Plantarum 1UHCC to degrade goat bone protein soaked in MRSB media. The indicators measured were lactic acid, pH, total bacteria, and total dissolved protein with different soaking times. This was conducted according to a completely randomized design (CRD) with three treatment duration of fermentation (24, 48 and 72 h, repectively) and three replications. The results showed that there was a significant effect (P<0.01) of the fermentation time on lactic acid, pH, total bacteria, dissolved protein value. Lactic acid concentration at 24 h fermentation time was 0.954±0.001% and this values was decreased to 0.821±0.092% after fermented for 48 h, but showed a significant increase at 72 h (0.942±0.002%). The pH value at 24-hour incubation were 5.413±0.015 then increased to 6.600±0.044 at 48 h of incubation; and decreased to at 72 h 6.303±0.266 at 72 h. Total bacterial values showed an increase in fermentation time of 24 h, 48 h and 72 h respectively were 8.248±0.196; 9.475±0.274 ; 9666±0.236 (log10CFU/mL). The value of dissolved protein showed an increase of 31.170±0.120 mg/mL; 31.183±0.101 mg/mL; 32.707 ±0.115mg/mL. This study indicated that 72 h fermentation time showed better quality of partial hydrolysis in goat bones.